Effects of a Newly Developed Early Post-hatch Feed for Poultry Hatchlings on the Performance of Poultry - Toshiaki Suzuki; Junko Noguchi; Masao Kitamura; Hirokazu Fujisaki (The Journal of Poultry Science, 2008)
Usually, 24h or sometimes more are necessary for hatchlings to arrive at farms after hatching. During this period, the chicks are supplied neither feed nor water. To overcome the disadvantages caused by the long-term fasting, a new early post-hatch feed named ‘Chick-aide’ was developed, which was moistened before use and used in hatcheries and at farms. Extruded pellets of 2.5mm in diameter were produced using natural feed ingredients. This contained 3.05McalME/kg, 30.7%CP and 11.2%CF at mash base before extrusion. Chicks were usually supplied with 200g of ‘Chick-aide’ per 100 birds in the hatcheries and 100g at farms. With the trials in experimental houses, ‘Chick-aide’ increased intestinal weight of newly hatched layer male chicks by 62.4 or 42.0% at 24h after feeding, compared to the 24h fasted group. Intestinal length was also increased by 12.6%. The chicks supplied with ‘Chick-aide’ on the day of hatch and after 24h at farms showed increased body weight by 5.7% at 1 week and 4.4% at 2 weeks age compared to the control. In a field trial with 10,000 layer hatchlings, ‘Chick-aide’ increased body weight by 6.9% at 1 week age in comparison to control chicks treated in a customary manner. Other field trials with 10,000 small sized broilers produced by immature breeders and 9,400 ordinary broilers showed that the body weight of small male chicks was increased by 150g at nearly shipping age (51 days) and that of ordinary chicks by 190g (52 days) with ‘Chick-aide’, compared to the control. The results showed that ‘Chick-aide’ developed intestine of early post-hatch chicks remarkably and improved the subsequent growth. Benefit vs cost calculation for broilers suggested that ‘Chick-aide’ was cost-effective. The early post-hatch feeds such as ‘Chick-aide’ which supply hatchlings with nutrients and water together are considered to be essential for the maximum poultry performance.